The contribution of public law to achieving sustainable development - Khaleel Ali Fadhel ALkaddoli (Peerian Journals Publishing, 2025)
Sustainable development is a controversial issue within the framework of international public law. This is due to the lack of a precise definition of its concept and scope of application. However, the idea of sustainable development has gained significant influence and interest from members of the international community, especially after the United Nations Conference on Environment and Development in Rio de Janeiro in 1992 (Rio Conference). This has been clearly reflected in many international conventions that have used the term sustainable development and other terms emanating from it, such as sustainable use, sustainable utilization, sustainable production, and sustainable management. This diversity in the terms used has created a kind of confusion and lack of clarity regarding the concept of sustainable development and the scope of its legal effect, as well as its objectives and legal principles within the framework of international law. Hence, the pivotal role of our study, which clarifies the contribution of international law to achieving sustainable development, is evident.
Keywords: Development; support for sustainable development; environment